Corrosion-fatigue life prediction of reinforced concrete square piles in marine environments. (August 2022) - Shao, Wei; Wang, Yongxin; Shi, Danda
Highlights: A three-stage model of corrosion-fatigue life prediction is established. A two-dimensional diffusion equation of chloride ions is presented. A rate competition model is established to predict the transition time from corrosion pits to cracks. A crack growth model is proposed to evaluate the crack growth time. Abstract: In this paper, a three-stage model of the corrosion-fatigue life prediction of reinforced concrete square piles in marine environments is established. First, a two-dimensional diffusion equation of chloride ions is presented. A simplified corrosion pit model is given to estimate the pit nucleation time. Second, according to the principle of competition between the growth rate of corrosion pits and the growth rate of cracks, a rate competition model is proposed. Third, a crack growth model is established based on the Paris-Erdogan equation. Finally, an example is illustrated to verify the validity of the model, and a parametric analysis of the main influencing factors is conducted. The analysis results show that the corrosion-fatigue life decreases with increasing surface chloride concentration, chloride diffusion coefficient, concrete compressive strength, reinforcement stress range, reinforcement diameter and cyclic load frequency. The corrosion-fatigue life increases as the critical chloride concentration and concrete protective layer thickness increase.